Possible Involvement of Liver Resident Macrophages (Kupffer Cells) in the Pathogenesis of Both Intrahepatic and Extrahepatic Inflammation - Yuki Kakinuma; Takuya Kimura; Yoshifumi Watanabe (Canadian Journal of Gastroenterology and Hepatology)
Liver resident macrophages designated Kupffer cells (KCs) form the largest subpopulation of tissue macrophages. KCs are involved in the pathogenesis of liver inflammation. However, the role of KCs in the systemic inflammation is still elusive. In this study, we examined whether KCs are involved in not only intrahepatic inflammation but also extrahepatic systemic inflammation. Administration of clodronate liposomes resulted in the KC deletion and in the suppression of liver injury in T cell-mediated hepatitis by ConA as a local acute inflammation model, while the treatment did not influence dextran sulfate sodium- (DSS-) induced colitis featured by weight loss, intestinal shrink, and pathological observation as an ectopic local acute inflammation model. In contrast, KC deletion inhibited collagen-induced arthritis as a model of extrahepatic, systemic chronical inflammation. KC deleted mice showed weaker arthritic scores, less joint swelling, and more joint space compared to arthritis-induced control mice. These results strongly suggest that KCs are involved in not only intrahepatic inflammatory response but also systemic (especially) chronic inflammation.